2000
DOI: 10.1088/0022-3727/33/8/315
|View full text |Cite
|
Sign up to set email alerts
|

Diamond polishing: the dependency of friction and wear on load and crystal orientation

Abstract: Results are presented of friction and wear measurements during diamond polishing using new instrumentation designed and built in our laboratory. The wear rates are found to be highly anisotropic, depending both on the crystallographic plane and on the direction along which sliding occurs. Friction measurements performed during polishing on a {100} plane in the 100 direction (the direction of the highest wear rate on the plane) and the 110 direction (the direction of the lowest wear rate) exhibit similar trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Monocrystalline diamonds are used for two reasons: (i) single crystals can be ground and polished yielding extremely sharp and flawless edges with radii less than 75 nm [8] and (ii) wear of the cutting edge is almost negligible when cutting non-ferrous metals and selected plastics and semiconductors. The anisotropy of the abrasive wear of diamond [9] must be observed in tool design, because tool life also depends on the hardness of the tool's rake face. Evans [10] and Marsilius [11] summarized the milestones in the evolution of diamond machining as follows.…”
Section: Diamond Machiningmentioning
confidence: 99%
“…Monocrystalline diamonds are used for two reasons: (i) single crystals can be ground and polished yielding extremely sharp and flawless edges with radii less than 75 nm [8] and (ii) wear of the cutting edge is almost negligible when cutting non-ferrous metals and selected plastics and semiconductors. The anisotropy of the abrasive wear of diamond [9] must be observed in tool design, because tool life also depends on the hardness of the tool's rake face. Evans [10] and Marsilius [11] summarized the milestones in the evolution of diamond machining as follows.…”
Section: Diamond Machiningmentioning
confidence: 99%
“…As such, many attempts have been made to understand the nature and composition of wear debris from both friction and polishing experiments. Analyses have variously included such techniques as infrared absorption (IR) spectroscopy [11,21], energy dispersive X-ray analysis (EDX) [9,21], X-ray diffraction [11,21], Raman spectroscopy [21] and various forms of microscopy in conjunction with electron energy loss spectroscopy (EELS) [9,12,13,19,20], electron diffraction [11] and analytical chemical tests [5,11]. All analyses concluded that the result of frictional sliding either during polishing or at low speed involving diamond-diamond contact is the formation of non-diamond wear debris.…”
Section: Post-wear Analysismentioning
confidence: 99%
“…Perhaps as a result of this, research on diamond wear has tended to branch into two main areas: low speed frictional sliding experiments -measuring friction with controlled contact and atmospheric conditions [5][6][7][8][9][10][11][12][13] and post-wear analysis which has included studies of the diamond surfaces after polishing and friction experiments [14][15][16][17] and debris analysis [9,11,12,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Nevertheless, the friction and wear of nanocrystalline diamond are quite anisotropic and depends on various factors, such as the chemical reactivity of the surface, crystallite size, crystallographic orientation, existence of dangling covalent bonds, sliding direction of oriented planes, surface roughness, properties of transfer layers, test environment and finally test parameters which influence the wear behavior, such as load and sliding velocity. 8,[11][12][13][14][15] In addition to all known important factors and tribological test parameters which may influence the wear behavior of the NCD films, the amount of hydrogen and sp 3 /sp 2 bonding ratio play a dominant role in the friction and wear performances of these materials. 16 There are several physical and chemical methods to synthesize NCD films.…”
Section: Introductionmentioning
confidence: 99%